KOMPARASI MODEL KEBANGKRUTAN PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novietta, Liza; Minan, Kersna (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
This research purpose to compare the bankrutpcy model : model Altman Z-Score, Ohlson and Zmijewski, to find out the different in prediction of bankrupcyt for textile and garmen industries that listed at Indonesia Stock Exchange from 2011 â 2014. Data analysis method is Paired Samples T-Test. Financial ratio analysis is used in every bankruptcy model and Paired Sample T-Test with the purpose to know the different of the prediction result from each model in the research. The results is no different between Altman vs Ohlson, Altman vs Zmijewski even Ohlson vs Zmijewski from 2011-2014.Keywords : financial ratio, analysis, bankruptcy